Naudts-like duality and the extreme Fisher information principle - Chimento, Luis Pascual (2000)
We show that using Frieden and Soffer’s extreme information principle [Phys. Rev. E 52, 2274 (1995)] with a Fisher measure constructed with escort probabilities [C. Beck and F. Schlögel, Thermodynamics of Chaotic Systems (Cambridge University Press, Cambridge, England, 1993)], the concomitant solutions obey a type of Naudts’s duality (e-print cond-mat/990470) for nonextensive ensembles [C. Tsallis, in Nonextensive Statistical Mechanics and its Applications, Lecture Notes in Physics, edited by S. Abe and Y. Okamoto (Springer-Verlag, Berlin, in press)]. © 2000 The American Physical Society.